Studies on the Use of Nondestructive Method Using VIR-NIR Spectroscopy for Color Determination of Blood Oranges Flesh - Diding Suhandy (Jurusan Teknologi Pertanian, 2014)
In this research, the potentiality of using NIR spectroscopy and chemometrics for nondestructive determination of blood oranges flesh was investigated. Spectra of intact blood oranges fruit were acquired using a VIS-NIR MMS1 portable spectrometer in absorbance mode. The RGB of blood oranges cut flesh was measured using image processing software.Â The calibration and validation models were developed using PLS regression using original spectra. The calibration results showed that the developed calibration models were promising with correlation r=0.82 for red component (R) determination and r=0.81 for green component (G) determination, respectively.Â Keywords: blood oranges, NIR spectroscopy, RGB color, absorbance mode, nondestructive method